Evaluation on solar-biogas heating system for buildings: Thermal characteristics and role of heat storage sectors - Liu, Zemin; Gao, Xinyu; Huang, Xinyu; Xie, Yuan; Gao, Jiayi; Yang, Xiaohu; He, Qiusheng (Applied energy, 2025)
Biogas serves as one of the representative biomass energies, providing clean and low-carbon circular energy product. It can be utilized in conjunction with renewable energy sources such as solar energy, and play a positive role in carbon neutrality and energy transition. Furthermore, the stability and flexibility of solar-biogas heating system can be improved by thermal storage device, hence the thermal performance of the thermal storage device becomes the research focus. In this paper, the numerical model of phase-change heat storage unit is established, and the temperature development and heat release features for the heat storage tank are explored under a rotational condition. Results reveal that the optimal (Model A1) complete solidification time is 26,554 s shorter than the original design, and 79.57 % less than the Model D1. In addition, Tactical Unit Algorithm is developed to optimize the heat storage capacity for the whole solar-aided biogas heating system for case study in buildings. Case study demonstrates that a solar collector area of 515 m2 and 580 heat storage tanks achieve supply-demand equilibrium, proving economically beneficial with a payback period of approximately 7 years, and reduced carbon emissions by about 100 tCO2e. [Display omitted] •Thermal storage is integrated into multi-energy complementary heating system.•Melting process under rotating conditions is justified in building heating system.•Effects of pore parameters of metal foam on melting performance are evaluated.•Tactical Unit Algorithm is developed to optimize building heating system.•Operation strategy under supply and demand balance is proposed.